2021
DOI: 10.3332/ecancer.2021.1269
|View full text |Cite
|
Sign up to set email alerts
|

Systematic SARS-CoV-2-testing for asymptomatic cancer patients treated at a public healthcare tertiary centre in Brazil

Abstract: Background:The coronavirus disease (COVID-19) pandemic has had enormous consequences in Brazil and worldwide. Patients with cancer affected by COVID-19 are at a higher risk of developing complications and worse outcomes compared to the noncancer population, particularly the ones on active systemic treatment. Considering the COVID-19's high transmissibility in asymptomatic and pre-symptomatic patients, we sought to determine the prevalence of COVID-19 infection in patients with solid cancers receiving systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… 14 , 21 , 22 Low seroconversion rates may be explained by a combination of factors other than immunosuppression in patients with cancer undergoing oncologic treatment, mostly asymptomatic infections, mild disease severity, serologic assay targeting nucleocapsid antigens, and a delayed single measurement after diagnosis. 12 , 23 , 24 Accordingly, we concluded that IgG determination is an unreliable way to estimate past infection rates in this specific clinical scenario.…”
Section: Discussionmentioning
confidence: 89%
“… 14 , 21 , 22 Low seroconversion rates may be explained by a combination of factors other than immunosuppression in patients with cancer undergoing oncologic treatment, mostly asymptomatic infections, mild disease severity, serologic assay targeting nucleocapsid antigens, and a delayed single measurement after diagnosis. 12 , 23 , 24 Accordingly, we concluded that IgG determination is an unreliable way to estimate past infection rates in this specific clinical scenario.…”
Section: Discussionmentioning
confidence: 89%